CPAP caps are associated with restricted head growth and altered skull morphology in newborn infants - Jacob, Sebastian; Wetzel, Nancy; Bläser, Annett; Thome, Ulrich Herbert; Ascherl, Rudolf Georg (Frontiers in Pediatrics, 2025)
BackgroundContinuous positive airway pressure (CPAP) devices for preterm infants are commonly affixed using snug-fitting caps. Monitoring of head growth is standard practice in preterm infants, as stagnant head growth has been associated with impaired neurodevelopmental outcome. However, a stagnant head circumference may not mean stagnant head growth since vertical head distortion has been repeatedly observed. Previously established centiles for ear-to-ear distances and head volume indices allow the evaluation of three-dimensional head growth. We hypothesized that CPAP duration may be associated with restricted head circumference gain, altered skull morphology, and possibly neurodevelopment.Patients and methodsAll 4590 infants treated with CPAP in the neonatal wards of Leipzig University Medical Center between 2009 and 2020 were included in our study. Body weight, body length, occipitofrontal head circumference (OFC), and transvertical (vEED) and transfontanellar ear-to-ear (fEED) distances were measured repeatedly. Head eccentricity (ECC) (a measure of disproportional head growth) and head volume indices (HVI) were calculated. Anthropometric data were z-transformed. A total of 367 infants were followed up for assessment of neurodevelopmental outcomes using the Bayley Scales of Infant and Toddler Development (third edition). Associations between cumulative cap time and anthropometric data were examined using unconditional growth models with linear mixed effects. Associations between head growth development and neurodevelopmental outcome were examined by correlating individual regression slopes of anthropometric data with Bayley scores.ResultsCumulative cap time was negatively associated with z-scores of OFC (β=−1.32×10−2, p<0.005), vEED (β=−6.65×10−3, p<0.005], fEED (β=−1.05×10−3, p>0.05), and HVI (β=−1.59×10−2, p<0.005), while it was positively associated with ECC (β=5.18×10−3, p<0.005). Individual OFC z-score slopes show low correlation with cognition (R = 0.07), language (R = 0.06), and motor (R = 0.01) Bayley scores. Individual vEED z-scores slopes show low correlation with cognition (R = −0.10), language (R = −0.08), and motor (R = −0.07) Bayley scores.ConclusionCPAP caps are associated with vertical and horizontal head growth restriction and altered infant head morphology, as indicated by increasing eccentricity. The correlation of the altered growth pattern with neurodevelopmental outcome was negligible. Our findings have clinical implications for the assessment of head growth development during CPAP therapy.